Formation of Neutral Peptide Aggregates as Studied by Mass‐Selective IR Action Spectroscopy. Issue 31 (28th June 2019) - Bakels, Sjors; Porskamp, Sebastiaan B. A.; Rijs, Anouk M.
Abstract: The spontaneous aggregation of proteins and peptides is widely studied owing to its relation to neurodegenerative diseases. To understand the underlying principles of peptide aggregation, elucidation of structure and structural changes upon their formation is key. This level of detail can be obtained by studying the peptide self‐assembly in the gas phase. Structural characterization of aggregates is mainly done on charged species, as adding charges is an intrinsic part of the technique to bring molecules into the gas phase. Studying neutral peptide aggregates will complement the existing picture. These studies are restricted to dimers due to experimental limitations. Herein, we present advances in laser desorption molecular beam spectroscopy to form neutral peptide aggregates consisting of up to 14 monomeric peptides in the gas phase. The combination of this technique with IR–UV spectroscopy allowed us to select each aggregate by size and subsequently characterize its structure. Abstract : Growing aggregates on the fly : The largest isolated neutral peptide aggregates were grown by using laser desorption molecular beam techniques. Infrared action spectroscopy was employed to visualize their predominantly parallel β sheet type structures.